2018
DOI: 10.22161/ijaers.5.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater quality:Study of the Nitrate(NO3-) concentration in the Urban Area of the Brazil/Bolivia Border

Abstract: Objective: To analyze the quality of groundwater potentially impacted by nitrate (NO3 -), before and after the flooding of the Madeira River, in two urban areas of Rondônia on the Brazil / Bolivia border. Method: Data and water samples were collected according to Standard Methods for the Examination for Water and Wasterwater (APHA, 1998) together with the methodology proposed in the Water Sample Collection and Preservation Environmental Sanitation -CETESB. The place were georeferenced using the Global Positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Several studies endorse the scenarios found in the research. According to a study by Paraguassú-Chaves et al [19], urban groundwater used by the population for human consumption and other uses is impacted by high levels of N nitrate (NO3-). Seventy-three percent (73%) of the samples had contents> 10 mg / L of nitrate.…”
Section: Ethical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies endorse the scenarios found in the research. According to a study by Paraguassú-Chaves et al [19], urban groundwater used by the population for human consumption and other uses is impacted by high levels of N nitrate (NO3-). Seventy-three percent (73%) of the samples had contents> 10 mg / L of nitrate.…”
Section: Ethical Aspectsmentioning
confidence: 99%
“…The study "Nitrate Contamination of Ground Water: sources and potential health effects" by Bouchard, Willians, Surampalli [22], confirms this real situation and its effects on human health. In a paper published in the "International Journal of Research and Science in Advanced Engineering", Paraguassú-Chaves et al [19] and another research result published in the journal "Debate in Action: scientific debate", Paraguassú-Chaves et al [23] demonstrate that urban groundwater in the city of Porto Among the conditions that aggravate the situation of water contamination by N nitrate (NO3-) in the urban area, is the inefficiency of basic sanitation (water supply and collection of sanitary sewage, construction of a rudimentary and septic tank in a precarious state). Queiroz, Heller, Silva [27], states that abundant and quality water is essential for public health, preventing diseases such as diarrhea and intestinal infections.…”
Section: Ethical Aspectsmentioning
confidence: 99%